Penerapan Program Penguatan Pendidikan Karakter di SD IT Mujahidul Amin Palangka Raya - Zahra Zahra; Heni Elia Wati; Hadma Yuliani; Slamet Riyadi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The implementation of strengthening character education is the most important effort in achieving national education goals. Given the importance of character education, in learning, educators must try to introduce and develop character education to students. This article aims to describe the implementation of the character education strengthening program at SD IT Mujahidul Amin Palangka Raya. The research method used is descriptive qualitative method, through data collection techniques of observation, interview, and documentation. The results showed that strengthening character education was formed through two activities, namely: strengthening character education integrated learning through exemplary (smile, greeting, greeting) and reading al-qur'an habituation program. Thus, the implementation of strengthening character education at SD IT Mujahidul Amin Palangka Raya has been carried out effectively, as a madrasah that not only excels in academic achievement.